2018
DOI: 10.15171/ijbsm.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Zinc Oxide Nanoparticles on Mupirocin-Resistant Staphylococcus aureus Isolated From Nasal Carriers

Abstract: Background: Staphylococcus aureus is one of the main human pathogens which should be taken into account as one of the main hospital infections due to its colonization in the nose of carrier personnel.The present study aims to determine the frequency of resistance to mupirocin in the hospital carriers of Staphylococcus aureus, and to investigate the antimicrobial effect of Zinc Oxide nanoparticles on the growth of resistant strains. Methods: In this cross-sectional study, samples were taken from the anterior n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous investigations have similarly established nanoparticles of smaller dimensions (> 100 nm) exhibit superior antimicrobial properties. In the current investigation, the utilization of AuNPs with a size of 30 nm exhibited noteworthy antibacterial activity, surpassing that observed in prior studies [29][30][31]. Grace et al (2007) demonstrated the efficacy of AuNPs against Grampositive and Gram-negative bacteria [32].…”
Section: Fig 1 Comparison Of Mean Absorbance At 570 Nm In Drug-resist...contrasting
confidence: 55%
“…Previous investigations have similarly established nanoparticles of smaller dimensions (> 100 nm) exhibit superior antimicrobial properties. In the current investigation, the utilization of AuNPs with a size of 30 nm exhibited noteworthy antibacterial activity, surpassing that observed in prior studies [29][30][31]. Grace et al (2007) demonstrated the efficacy of AuNPs against Grampositive and Gram-negative bacteria [32].…”
Section: Fig 1 Comparison Of Mean Absorbance At 570 Nm In Drug-resist...contrasting
confidence: 55%
“…However, the authors in [67] reported that TiOPs had no antibacterial effect. Many authors have reported antibacterial effects of ZnONPs against several isolates, such as Staphylococcus sp., [68] methicillin-resistant Staphylococcus aureus, [69], Pseudomonas sp. [70] and Escherichia coli [71].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 31 (18.9%) of the hospital staff were nasal carriers of S. aureus. As reported by researchers in Iran in 2010 (18) and 2018 (19), 32% and 26.8% of the hospital staff were carriers of S. aureus. It was higher than the amount found in the present study.…”
Section: Discussionmentioning
confidence: 78%